2005
DOI: 10.1007/s11240-005-9015-9
|View full text |Cite
|
Sign up to set email alerts
|

Direct plant regeneration from cultured young leaf segments of sugarcane

Abstract: Young leaf segments (1.0-1.5 cm) excised from spindle explants of three commercial sugarcane varieties viz. Co J 64, Co J 83 and Co J 86 were cultured on different media compositions based on Murashige and Skoog (1962) salts. Cultured explants exhibited swelling followed by direct shoot regeneration on media containing naphthaleneacetic acid, in all the three varieties. Highest frequency 83.12% shoot regeneration occurred on Murashige and Skoog medium supplemented with naphthaleneacetic acid (5.0 mg l )1 ) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0
4

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 11 publications
(7 reference statements)
0
25
0
4
Order By: Relevance
“…This result can be explained with the presence of predetermined cells which first dedifferentiate themselves, subsequently form new meristematic centres, and finally differentiate again producing new organs [34][35][36][37][38][39]. This process, due to cell totipotency, has been observed in several species [30,[40][41][42][43][44][45][46][47] and is very efficient for regeneration. Our results showed that AFLP is a very sensitive and reliable molecular marker technique for revealing specific genomic alterations induced by tissue culture and for identifying slightly different genotypes.…”
Section: Discussionmentioning
confidence: 99%
“…This result can be explained with the presence of predetermined cells which first dedifferentiate themselves, subsequently form new meristematic centres, and finally differentiate again producing new organs [34][35][36][37][38][39]. This process, due to cell totipotency, has been observed in several species [30,[40][41][42][43][44][45][46][47] and is very efficient for regeneration. Our results showed that AFLP is a very sensitive and reliable molecular marker technique for revealing specific genomic alterations induced by tissue culture and for identifying slightly different genotypes.…”
Section: Discussionmentioning
confidence: 99%
“…O mesmo ocorreu para o clone RB986419. A manutenção da alta umidade relativa, desde a retirada dos explantes do meio de cultivo até a retomada de seu crescimento, é fator de extrema importância para a sua sobrevivência (GRATTAPAGLIA; MACHADO, 1990).…”
Section: Fonte: Mudry (2011)unclassified
“…Lack of suitable multiplication procedures, for the mass multiplication of the elite germplasm, results in varietal decline (Kaur and Kapoor, 2016). The yield potential of sugarcane varieties is deteriorating, due to susceptibility to diseases, insects, admixture and changing edaphic and climatic environment (Gill et al, 2006). Moreover, the lack of rapid multiplication procedures has long been a serious problem in sugarcane breeding programs, as it takes 10-15 years of work to complete a selection cycle.…”
Section: Introductionmentioning
confidence: 99%